Rock and paleomagneitc measurements of PS67/197-1 - Xiao, Wenshen; Frederichs, Thomas; Gersonde, Rainer; Esper, Oliver; Zhang, Xu (PANGAEA, 2025)
The core was taken in 2005 during Polarstern cruise ANT-XXII/4 in the central Scotia Sea. Magnetic susceptibility, further paleomagnetic information and other proxies were measured on this and other cores in order to establish a detailed sediment stratigraphy of the Scotia Sea for the past 300 ka. A description of the methods is given in Xiao et al. (2016).
Keywords: Inclination; Magnetic susceptibility; Marine sediment; Natural remanent magnetization (NRM); Paleomagnetics; Relative paleointensity (RPI); Scotia Sea; Southern Ocean